Stimulation of the noradrenergic system enhances and blockade reduces memory for emotional material in man. - O'Carroll, R; Drysdale, E; Cahill, L; Shajahan, P; Ebmeier, K (1999)
BACKGROUND: It is clearly established that emotional events tend to be remembered particularly vividly. The neurobiological substrates of this phenomenon are poorly understood. Recently, the noradrenergic system has been implicated in that beta blockade has been shown to reduce significantly the delayed recall of emotional material with matched neutral material being unaffected. METHODS: In the present study, 36 healthy young adults were randomly allocated to receive either yohimbine, which stimulates central noradrenergic activity, metoprolol which blocks noradrenergic activity, or matched placebo. The three groups were well matched. All capsules were taken orally, prior to viewing a narrated 11 slide show described a boy being involved in an accident. RESULTS: Yohimbine significantly elevated, and metoprolol reduced mean heart rate during the slide show relative to placebo, thus confirming the efficacy of the pharmacological manipulation. One week later, in a surprise' test, memory for the slide show was tested. As predicted, yohimbine-treated subjects recalled significantly more and metoprolol subjects fewer slides relative to placebo. This result was confirmed via analysis of multiple-choice recognition memory scores. CONCLUSIONS: We conclude that stimulation of the noradrenergic system results in the enhancement and blockade in a reduction of recall and recognition of emotional material in man.